2021
DOI: 10.1038/s41598-021-00834-1
|View full text |Cite
|
Sign up to set email alerts
|

Developmental capacity is unevenly distributed among single blastomeres of 2-cell and 4-cell stage mouse embryos

Abstract: During preimplantation development, mammalian embryo cells (blastomeres) cleave, gradually losing their potencies and differentiating into three primary cell lineages: epiblast (EPI), trophectoderm (TE), and primitive endoderm (PE). The exact moment at which cells begin to vary in their potency for multilineage differentiation still remains unknown. We sought to answer the question of whether single cells isolated from 2- and 4-cell embryos differ in their ability to generate the progenitors and cells of blast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Several studies have shown that blastomeres isolated from most precompaction embryos differ in their ability to form TE, EPI, and PE cells, indicating their unequal developmental potential ( Krawczyk et al, 2021 ; Maemura et al, 2021 ). A developmental bias among sister blastomeres has also been reported in intact 4-cell and 8-cell mouse embryos, in which lineage tracing experiments demonstrated that most individual embryos contain blastomeres exhibiting biased and unbiased contribution patterns to TE and ICM and their derivatives ( Tabansky et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have shown that blastomeres isolated from most precompaction embryos differ in their ability to form TE, EPI, and PE cells, indicating their unequal developmental potential ( Krawczyk et al, 2021 ; Maemura et al, 2021 ). A developmental bias among sister blastomeres has also been reported in intact 4-cell and 8-cell mouse embryos, in which lineage tracing experiments demonstrated that most individual embryos contain blastomeres exhibiting biased and unbiased contribution patterns to TE and ICM and their derivatives ( Tabansky et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this biological constraint, the plasticity of embryonic development and the presence of signaling modulators in the derivation medium should also be considered when interpreting the results of our study. Blastomeres of 8-cell embryos show impaired ability to form pluripotent EPI cells after isolation and culture in standard embryo culture medium, and they tend to develop as trophoblastic vesicles instead of forming blastocysts ( Krawczyk et al, 2021 ; Maemura et al, 2021 ). This could be attributed to the lack of cell-cell contacts and positional information, which was shown to induce blastomeres to change their gene expression pattern towards a unique pattern characteristic of neither ICM nor TE, but with a tendency to mimic that of TE cells ( Lorthongpanich et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the development of early embryos is punctual and regular, what mechanisms drive the switching between different lineage patterns and adjust the mismatch between the position and fate of a certain cell? In view of the powerful cell totipotency and embryonic plasticity in mouse 2- and 4-cell embryos [96] , [97] , [98] , whether the molecular asymmetry can be inherited or reconstructed in new 2- and 4-cell embryos developed from “half”- and “one-quarter”-cleaving embryos is an exciting scientific question waiting to be explored. The answers to these questions will provide a clear view of the detailed mechanisms for early cell fate regulation.…”
Section: Concluding Remarks and Perspectivesmentioning
confidence: 99%
“…Each dissociated blastomere would develop into a pluteus larva, albeit not always of the same size, and this behavior seemed to relate to how the plane of 1 st cleavage was oriented. From 2017 onwards, increasing evidence has been showing that when mouse blastomeres are separated at the 2-cell stage, only one blastomere is able to develop into a viable blastocyst or develop fully into a live mouse in most cases (Casser et al ., 2017; Krawczyk et al ., 2021; Maemura et al ., 2021). Full developmental potential is probably attained when the blastomere progeny accrues sufficient epiblast cells by the blastocyst stage (Morris et al ., 2012).…”
Section: Introductionmentioning
confidence: 99%